Table Amphorae from Augusta Traiana (Thrace) - Roussev, Nikolay (Rei Cretariae Romanae Fautorum Acta, 2022)
Many years of excavation on the territory of Augusta Traiana in the province of Thrace have yielded a significant number of so-called “table amphorae”. Several Roman and Late Roman types are described below. Almost all artifacts are from rescue excavations in the territory of the city and its necropolis. Of seven type recognized, three can be dated to the Roman period and four to the Late Roman. Oats found in some vessels raise questions of cooperative transport and table function of the group. Another question concerns the production on such vessels. Comparanda and dates come from several Roman towns and from other sites in the hills, where table amphorae provide over 50% of the total amphorae.